Pendekatan Teologi Kontekstual Terhadap Penggunaan Teknologi AI dalam Ibadah bagi Mahasiswa Fakultas Teologi UKIT - Kalalo, Jefry; Limbah, Ilona Apriningsih (Educatio Christi, 2024)
This article contains information about the development of artificial intelligence (AI) technology that has brought significant changes in various aspects of life, including the practice of worship among students of the Faculty of Theology UKIT. This research aims to explore contextual theological approaches to the use of AI in worship, taking into account the challenges and opportunities that this technology offers. The research method used is qualitative descriptive with a phenomenological approach, involving in-depth interviews with 10 informants consisting of AI users and non-users in worship. The results show that the use of AI can improve the accessibility and relevance of worship materials, but it also raises concerns about the authenticity of spiritual experiences and the depth of interpersonal relationships within faith communities. This research emphasizes the importance of a contextual theological approach in understanding the use of AI as a tool that can enrich the worship experience without compromising the values of the Christian faith. Thus, it is hoped that theology students can become leaders who are responsive to the development of the times, as well as firmly rooted in faith.